Physical Activity and Systemic Lupus Erythematosus Among European Populations: A Two-Sample Mendelian Randomization Study - Huang, Shuo; Tian, Fengyuan; Yang, Xiaoxuan; Fang, Sijia; Fan, Yongsheng; Bao, Jie (Frontiers in Genetics, 2022)
Background: The causal relationship between physical activity (PA) and systemic lupus erythematosus (SLE) remains uncertain. We aimed to explore the causal effect of PA on SLE by two-sample Mendelian randomization (MR) study. Methods: Summary statistics of SLE were obtained from a genome-wide association study (GWAS) of European descent, including 4,036 cases and 6,959 controls. Based on two additional GWAS, we selected genetic variants as instrumental variables (IVs) that were related to PA (MVPA, VPA, SSOE, average acceleration and sedentary behavior). The two-sample MR study was conducted to estimate causal relationship between PA and SLE, with the inverse-variance weighted (IVW) method, simple- and weighted-median method. Moreover, MR-Egger regression, MR-PRESSO and leave-one-out analysis was performed to evaluate the potential pleiotropy effect. Results: In the end, we totally selected 37 SNPs (15 SNPs for MVPA, 5 SNPs for VPA, 9 SNPs for SSOE, 5 SNPs for average acceleration, 3 SNPs for sedentary behavior). According to the IVW result, as the primary method of MR, we found that genetically predicted PA was not causally associated with risk of SLE (MVPA: OR 0.44, 95% CI 0.09-2.10, P = 0.305; VPA: OR 0.20, 95% CI 0.00-18.97, P = 0.490; SSOE: OR 0.96, 95% CI 0.03-29.24, P = 0.983; average acceleration: OR 0.91, 95% CI 0.79-1.05, P = 0.190; sedentary behavior: OR 1.54, 95% CI 0.35-6.81, P = 0.572). MR-Egger, MR-PRESSO and leave-one-out analysis did not indicate horizontal pleiotropy. Conclusions: Our MR study suggested that genetically predicted PA was not causally associated with SLE among the European population.